التواصل وعلاقته بالشعور بالوحدة النفسية لدى الأطفال ضعاف السمع - محمد، سعاد محمد عبدالمنعم (جامعة عين شمس - كلية البنات للآداب والعلوم والتربية, 2013)
يسعي البحث للكشف عن العلاقة الارتباطية بين التواصل والشعور بالوحدة النفسية لدى الأطفال ضعاف السمع، والكشف عن وجود فروق في مستوى التواصل ترجع لمتغير الجنس. والكشف عن وجود فروق في مستوى الشعور بالوحدة النفسية ترجع لمتغير الجنس. وتتضمن عينة البحث (26) من الأطفال ضعاف السمع من الجنسين منهم (14) ذكور، (12) إناث، وأعمارهم تراوحت ما بين (9-12) سنة، ودرجة الذكاء تراوحت ما بين (90-110) درجة، ودرجة قياس السمع تراوحت ما بين (٤٠- 69) درجة، وأسفرت النتائج عن وجود ارتباط موجب دال إحصائيا عند مستوي دلالة (0.01) بين التواصل والشعور بالوحدة النفسية لدى الأطفال ضعاف السمع. كما لا توجد فروق ذات دلالة إحصائية في مستوى التواصل بين الذكور والإناث. وأيضا لا توجد فروق ذات دلالة إحصائية في مستوى الشعور بالوحدة النفسية بين الذكور والإناث. Research seeks to reveal the correlation between the communication and psychological loneliness in Hard Hearing Children, and the detection of the existence of differences in the level of communication due to the variable sex. And detecting the presence of differences in the level of psychological loneliness due to the variable sex. The sample search includes (26) of Hard Hearing Children of both sexes of them (14) males, (12) females, and their ages ranged between (9-12 years), and the degree of intelligence ranged between 90-110 degrees, audiometry ranged between (40-69) degree. The results revealed the presence of a statistically significant correlation positive at the level of significance (0.01) between communication and psychological loneliness of Hard Hearing Children. There is also no statistically significant differences in the level of communication between the male and female. And also no statistically significant differences in the level of psychological loneliness between males and females.
Keywords: الصحة النفسية -- الرعاية الإجتماعية -- الإضطرابات النفسية -- الوحدة النفسية -- الأطفال ضعاف السمع